Cytogenetics abnormalities in acute leukemias of ambiguous lineage: First report of complex variant philadelphia translocations - Raghavendra HV; Mangala Gowri; Namrata NR; Lakshmiah KC (International Journal of Medical Research and Review, 2016)
Background: Acute leukemias of ambiguous lineage (ALAL) are incompletely characterized and are very rare, accounts< 4% of acute leukemias . In most leukaemias the cytogenetic and molecular genetic changes have emerged to be diagnostic as well as prognostic importance. Due to Lack of diagnostic criterias, it is difficult to establish cytogenetic features in ALAL. In present study we reviewed chromosomal aberrations, their molecular background, their prognostic relevance of ALAL & summarized some new chromosome aberrations along with probable mechanism of complex variant translocation.Design and Methods: Present study from Kidwai state cancer institute concentrated on cytogenetic findings of ALAL, especially B+Myeloid MPAL cases, more so regarding complex variant phildelphia chromosome translocations summarised diagnostic criteria based on WHO 2008 classification, clinical, immunophenotyping and molecular features, along with treatment & follow up.Results: Among 32 cases of ALAL cases, 28 MPAL cases reported in the present study 13 cases were B/Myeloid, followed by B+T MPAL, T+Myeloid .4 cases of undifferentiated and unclassifiable leukemias were reported. B/myeloid MPAL were in majority, 13 cases. Cytogenetics abnormality was detected in 4 cases of B/myeloid MPAL. 3 cases were Ph +, another case was hyperdiploid, surprisingly out of 3 Ph+ cases, 2 cases (66.6%) showed complex variant Phildelphia chromosome.Conclusion: B+MYELOID MPAL revealed significant cytogenetic abnormalities. Although Ph+ is reported in MPAL, complex variant Ph with 4 or 3 way translocations are not reported in ALAL especially in B/Myeloid MPAL .Immunophenotyping & cytogenetics in ALAL should be mandatory. Multiple levels of genetic heterogeneity exist in these leukemias with variant Ph translocations. Prognosis improves when treated with Imatinib.